Influenza vaccine effectiveness against hospitalization with laboratory-confirmed influenza in Greece: A pooled analysis across six seasons, 2013–2014 to 2018–2019. Issue 12 (10th March 2020) - Mouratidou, Elisavet; Lambrou, Angeliki; Andreopoulou, Anastasia; Gioula, Georgia; Exindari, Maria; Kossyvakis, Athanasios; Pogka, Vasiliki; Mentis, Andreas; Georgakopoulou, Theano; Lytras, Theodore
Highlights: We assessed influenza vaccine effectiveness in Greece from 2013 to 2019. We did a pooled test-negative analysis over six seasons. Vaccination reduced the risk of hospitalization with influenza by 45.5% Influenza vaccine was more effective for A(H1N1)pdm09 and B, and less for A(H3N2) Results confirm the public health benefit of seasonal influenza vaccination. Abstract: Background: Monitoring seasonal influenza Vaccine Effectiveness (VE) is key to inform vaccination strategies and sustain uptake. Pooling data across multiple seasons increases precision and allows for subgroup analyses, providing more conclusive evidence. Our aim was to assess VE against hospitalization with laboratory-confirmed influenza in Greece over six seasons, from 2013 to 2014 to 2018–2019, using routinely collected surveillance data. Methods: Swab samples from hospitalized patients across the country were tested for influenza by RT-PCR. We used the test-negative design, with patients testing positive for influenza serving as cases and those testing negative serving as controls. VE was calculated as one minus the Odds Ratio (OR) for influenza vaccination, estimated by mixed-effects logistic regression and adjusted for age, sex, hospitalization type (being in intensive care or not), time from symptom onset to swabbing, and calendar time. Stratified estimates by age and hospitalization type were obtained, and also subgroup estimates by influenza type/subtype and season. Antigenic and genetic characterization of a subset of circulating influenza strains was performed. Results: A total of 3, 882 test-positive cases and 5, 895 test-negative controls were analyzed. Across all seasons, adjusted VE was 45.5% (95% CI: 31.6–56.6) against all influenza, 62.8% against A(H1N1)pdm09 (95% CI: 40.7–76.7), 28.2% against A(H3N2) (95% CI: 12.0–41.3) and 45.5% against influenza B (95% CI: 29.1–58.1). VE was slightly lower for patients aged 60 years and over, and similar between patients hospitalized inside or outside intensive care. Circulating A(H1N1)pdm09 and B strains were antigenically similar to the vaccine strains, whereas A(H3N2) were not. Conclusion: Our results confirm the public health benefits from seasonal influenza vaccination, despite the suboptimal effectiveness against A(H3N2) strains. Continued monitoring of VE is essential, and routinely collected surveillance data can be valuable in this regard.